Decisions on Purchasing Halal-Certified Products among "Pantura Muslims" - Happy Sista Devy; Ismanto, Kuat (Journal of Islamic Economics Perspectives, 2023)
The halal industry is becoming a business trend in various countries worldwide, both in Muslim and non-Muslim countries. Indonesia is a country that actively participates in its development, even though developments in society have yet to be maximized. This article aims to explore the perceptions of the people of Pekalongan who have a religious character towards the decision to purchase halal-certified products. The research was conducted within a quantitative framework, and the data was collected through a questionnaire with a purposive sampling strategy obtained from 92 respondents. The collected data were analysed with the E-Views analysis tool. The decision to buy halal products is influenced by religiosity, halal knowledge, halal behaviours, and halal awareness by 48.5% simultaneously. Halal awareness and religiosity positively and significantly affect the decision to purchase halal products. The opposite condition is shown by the halal behaviours and knowledge variables, which have a positive but insignificant effect. This research implies that people with Islamic religious characteristics, awareness, and religiosity, which are internal, greatly influence purchasing decisions. The weakness of this research is that the respondents need to be expanded and added so they can produce more comprehensive conclusions.